(untitled) (Bangladesh Journal of Physiology and Pharmacology, 2009)
A randomized controlled trial was conducted in one unit of Gynecology and Obstetrics Dept. of a Govt. hospital by giving a single dose preoperative prophylactic antibiotic and the results were compared with a control group who received a conventional prophylactic regimen of antibiotic combination. A total of 60 samples were taken from the patients currently admitted and undergoing total abdominal hysterectomy in one unit of the Department of Obstetrics & Gynecology of a Govt. hospital for this trial and they were divided into two groups - 30 Cases and 30 Control. Case group were given a single dose cephradine 1 gm IV just before induction of anesthesia. Control group were given Inj. Ciprofloxacin 200 mg IV 12 hrsly plus inj. Metronidazol 500 mg 8 hrsly till oral feeding followed by oral tab. Ciprofloxacin 500 mg 12 hrsly plus tab. Metronidazol 400 mg 8 hrsly in the remaining days which was then practicing in that gynecology unit of the Govt. hospital. Variables measured for the trial were total cost and duration of antimicrobial therapy, rate of postoperative infection and side effects of antimicrobial therapy. While comparing the outcome between the case and control group, it was observed that both the duration and cost (P<0.001) and also the side effects (P<0.05) of antimicrobial therapy were significantly higher in control group than the case group (duration of antimicrobial therapy was 2.9± 0.88 days in case group and 8. 9±0.58 days in control group and cost of antimicrobial therapy was 113.06± 24.53 taka in case group and 957.376±32.05 taka in control group). But the rate of post operative infection which is the main objective of giving preoperative antibiotic prophylaxis, was significantly higher in case group than the control group (P<0.05). But this infection rate could be reduced if the sterilization procedure of the operation theatre and general conditions of the patients were improved. If these risk factors could be minimized, single dose preoperative prophylactic antibiotic could be effectively practiced in our country. DOI: 10.3329/bjpp.v22i1.3560 Bangladesh J Physiol Pharmacol 2006; 22(1/2) : 1-4